Effects of Phenol Addition on Oil Extraction from Moroccan Oil Shale by Supercritical Toluene - Abourriche, A.; Oumam, M.; Benhammou, A.; Mouiya, M.; El hafiane, Y.; Abouliatim, Y.; Nibou, L.; Hannache, H.; Birot, M.; Pailler, R.; Naslain, R. (Journal of Applied Solution Chemistry and Modeling, 2021)
In the present work, the effect of phenol on the supercritical extraction of the organic matter from Tarfaya’s oil shale with toluene was evaluated. The experimental results showed clearly that phenol had a significant effect on the yield and the composition of the oils obtained. Moreover, it was shown that phenol was a very efficient modifier for oil shale, giving a good yield of recovery and a suitable maturation of the organic matter. The pitches prepared by mixing phenol and toluene contain more aromatics and have a high char yield at 950 °C compared to those obtained by extraction with supercritical toluene alone.